2014
DOI: 10.2134/fg-2013-0001-rs
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Rate of Chaparral Treatment Affects Tall Fescue Seedhead Development and Pasture Plant Densities

Abstract: The herbicide, Chaparral, has been shown to suppress seedhead development in tall fescue (Lolium arundinaceum) pastures and reduce the symptoms of tall fescue toxicosis in cattle. However, little is known about the logistics of herbicide treatment on tall fescue pastures. The objective of this study was to determine the effect of three rates of Chaparral on tall fescue pasture when applied at three times (October, March, and April) during the growing season. Chaparral reduced seedhead densities of tall fescue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As indicated by the reductions in tall fescue leaf yield and tiller density, total biomass yield reduction at spring harvest can be attributed not to just seedhead suppression, but also reductions in tall fescue vegetative growth per unit area. Goff et al (2014) observed reductions in tall fescue crowns and increased presence of orchardgrass and Kentucky bluegrass in response to aminopyralid plus metsulfuron applied in early spring.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…As indicated by the reductions in tall fescue leaf yield and tiller density, total biomass yield reduction at spring harvest can be attributed not to just seedhead suppression, but also reductions in tall fescue vegetative growth per unit area. Goff et al (2014) observed reductions in tall fescue crowns and increased presence of orchardgrass and Kentucky bluegrass in response to aminopyralid plus metsulfuron applied in early spring.…”
Section: Resultsmentioning
confidence: 80%
“…In the same study, no differences were found within those treatments, also indicating that seedhead suppression can be achieved with lower rates of metsulfuron. Results from Kentucky studies have also shown aminopyralid plus metsulfuron reduces tall fescue seedheads (Aiken et al 2012;Goff et al 2014). Treatment with ACP plus 2,4-D resulted in higher seedhead density than the nontreated control.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…There was a tendency for orchardgrass to be greater (P=0.07) in the NEGCON, than the pastures receiving varying levels of Metsulfuron (MET0, MET67, MET134). Goff et al (2014) reported spring metsulfuron application to tall fescue pastures tended to increase the density of non-fescue cool season forage species (Kentucky bluegrass and orchardgrass) after one application. However, amongst other forage species recognized, botanical composition did not change (P>0.20) in response to treatment.…”
Section: Seedhead and Botanical Compositionmentioning
confidence: 94%